Marketized mentality, competitive/egoistic school culture, and delinquent attitudes and behavior: an application of institutional anomie theory - Groß, Eva (Criminology, 2018)
We analyze the individual‐level and school‐level determinants of delinquency through the lens of a macro‐sociological theory of crime—institutional anomie theory (IAT). The concept of a “marketized mentality” is introduced as a predictor of students’ delinquency, along with an egoistic/competitive school culture—a feature of the school community. Five hypotheses pertaining to the readiness to use violence and self‐reported delinquency were assessed using multilevel modeling with data from a survey in Germany for 4,150 students clustered in 69 schools. The results largely meet theoretical expectations. The measure of marketized mentality exhibits robust relationships with both forms of delinquency at the individual level, and an egoistic/competitive school culture helps explain variation in levels of these forms of delinquency across schools. Also consistent with expectations, the anti‐social effects of marketized mentality are accentuated for both the readiness to use violence and committing instrumentally motivated property offenses as a competitive/egoistic school climate increases. The results of our analyses reveal that bringing in concepts of IAT can appreciably enhance understanding of the characteristics of students and features of communal school organization that are conducive to youthful offending.